Acquired Senescent T-Cell Phenotype Correlates with Clinical Severity in GATA Binding Protein 2-Deficient Patients - Ruiz-García, Raquel; Rodríguez-Vigil, Carmen; Marco, Francisco Manuel; Gallego-Bustos, Fernando; Castro-Panete, María José; Diez-Alonso, Laura; Muñoz-Ruiz, Carlos; Ruiz-Contreras, Jesús; Paz-Artal, Estela; González-Granado, Luis Ignacio; Allende, Luis Miguel (Frontiers in Immunology, 2017)
GATA2 deficiency is a rare disorder of haematopoiesis, lymphatics and immunity caused by spontaneous or autosomal dominant mutations in the GATA2 gene. Clinical manifestations range from neutropenia, lymphedema, deafness, to severe viral and mycobacterial infections, bone marrow failure and acute myeloid leukaemia. Patients also present with monocytopenia, dendritic cell, B- and NK-cell deficiency. We studied the T-cell and NK-cell compartments of four GATA2 deficient patients to assess if changes in these lymphocyte populations could be correlated with clinical phenotype. Patients with more severe clinical complications demonstrated a senescent T-cell phenotype whereas patients with lower clinical score had undetectable changes relative to controls. In contrast, patients’ NK-cells demonstrated an immature/activated phenotype that did not correlate with clinical score, suggesting an intrinsic NK-cell defect. These studies will help us to determine the contribution of T- and NK-cell dysregulation to the clinical phenotype of GATA2 patients, and may help to establish the most accurate therapeutic options for these patients. Asymptomatic patients may be taken into consideration for hematopoietic stem cell transplantation when dysregulation of T cell and NK cell compartment is present.